AUDIO VISUAL MELALUI INSTAGRAM MEMPENGARUHI PENGETAHUAN PERSONAL HYGIENE SAAT HAID PADA SISWI KELAS X (Jurnal Kesehatan Siliwangi, 2021)
Adolescent Reproductive Health is a topic that needs to be known, especially for adolescents so that they have correct information about the reproductive process and the various factors that surround it.The increasing number of Reproductive Tract Infections (ISR), Cervical Cancer of 84.1 thousand people, becomes the basis for the need to increase knowledge about Personal Hygiene during Menstruation.The way that can be done to get knowledge is by using health promotion media. Health promotion media that can be used in the midst of the covid-19 pandemic or WFH are Audio Visual Media via Instagram.This study aims to determine the effect of audio-visual media through Instagram on the knowledge of adolescent girls about personal hygiene during menstruation. This research is a quantitative research with one group pretest-posttest design.The population consists of 217 teenage girls in class X at SMAN 1 Majalaya and a sample of 68 usingtechnique purposive sampling and measuring instruments using a questionnaire.Univariate analysis includes knowledge frequency distribution and Bivariate analysis usingtest Wilcoxon.The results of the study were obtained before being given audio-visual media through Instagram, most of them had sufficient knowledge, and increased after being given Audio Visual Media through Instagram, most of them had good knowledge. The results of the bivariate analysis showed the value of Asymp.Sig.(2-tailed) 0.000 < 0.05 then Ho was rejected, so it can be concluded that there is an Effect of Audio Visual Media through Instagram on the knowledge of young women about Personal Hygiene during Menstruation in class X in 2021.